Aluminium Roofing Products Ltd Marketing to the Public Sector, UK - Hosseini, Sadaf (2009)
This management project was undertaken on behalf of Aluminium Roofing Products Ltd ™ (ARP), a young, entrepreneurial company associated predominantly with aluminium products. The project brief was initially untaken by Ian Dunbar - one of the marketing segmentation gurus in the UK. As a result of his investigation, the company aimed to target the public sector in the UK in order to increase their market share. The project was fairly broad and identified several areas of the public sector which required investigation. The brief ranges from investigating the operational and strategic concerns to the viability of marketing to the public sector, studying relationships in different levels of the government with a view to understanding their marketing or buying behaviour. The author worked with ARP from June to September 2009 and during this time, attended numerous meetings, workshops and conferences in order to gain more knowledge about the processes of decision making in the authorities and also meet key stakeholders. Moreover, the author interviewed key stakeholders to establish their understanding of the aluminium products and also mapped out the key influencers and decision makers in buying processes. From this research findings several important issues have been identified that require the immediate attention of ARP. Although aluminium rainwater products have suffered from a low market share compared to their rival product (plastic) it is now experiencing a transformational stage. With ARP’s commitment, enthusiasm and great passion for being ‘socially responsible’ they will almost certainly experience growth which will in turn increase both their contribution to society and their appeal to a new and wider range of consumers.